2003
DOI: 10.1037/0003-066x.58.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous ideas: Five beliefs that propel groups toward conflict.

Abstract: The toll in death, suffering, and displacement caused by conflicts engaging groups defined by ethnicity, nationality, religion, or other social identities has reached staggering proportions over the past decade. With expertise in research and intervention, psychologists have critical contributions to make to more fully understanding and more effectively confronting this distressing global phenomenon. The authors focus on the parallels between the core beliefs of individuals and the collective worldviews of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
148
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(155 citation statements)
references
References 63 publications
5
148
0
2
Order By: Relevance
“…These sorts of considerations have led scholars to discuss the role of doubleminority demographics in specific cases of intergroup conflict (e.g., Eidelson & Eidelson, 2003;Ross, 1995). But, as yet, these speculations have not been buttressed by rigorous empirical inquiry.…”
Section: Double Minorities and Intergroup Conflictmentioning
confidence: 99%
“…These sorts of considerations have led scholars to discuss the role of doubleminority demographics in specific cases of intergroup conflict (e.g., Eidelson & Eidelson, 2003;Ross, 1995). But, as yet, these speculations have not been buttressed by rigorous empirical inquiry.…”
Section: Double Minorities and Intergroup Conflictmentioning
confidence: 99%
“…Examining the five belief domains highlighted by Eidelson and Eidelson (2003)-that is, vulnerability, injustice, distrust, superiority, and helplessness-we found that (a) compared to the pre-9/11 sample, post-9/11 respondents reported stronger group-level beliefs or perceptions about vulnerability, injustice, distrust, and superiority and a weaker group-level belief or perception about helplessness and (b) at the personal world level, post-9/11 respondents scored higher on beliefs about vulnerability and lower on beliefs about injustice and distrust than their pre-9/11 counterparts. …”
mentioning
confidence: 99%
“…In the intervening years, much progress has been made in delineating individual-group dynamics and their role in intergroup conflict (e.g., Bar-Tal, 1990;Deutsch, 1973;Ross, 1995;Sherif, 1966;Tajfel & Turner, 1986;Turner, Hogg, Oakes, Reicher, & Wetherell, 1987). In a recent analysis of the interplay between the individual and the group, Eidelson and Eidelson (2003) focused on a set of five beliefs that appear to play prominent roles at both the personal and the collective level-beliefs about vulnerability, injustice, distrust, superiority, and helplessness. Eidelson and Eidelson (2003) proposed that these specific belief domains are especially influential in reference to distress and strife at both the interpersonal and intergroup levels, serving as triggers for or constraints on personal or collective action aimed at altering unsatisfying circumstances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…"Everyone knows that 'they' are out to get us." Eidelson & Eidelson (2003) see clear parallels between individual core beliefs and those of collectives (the latter they call "worldviews"); in both cases these beliefs can be destructive-for the paranoid individual who fears others or for the group whose fears propel it toward conflict. In both cases, information acquisition and processing are strongly biased by these core beliefs, and in both cases judgments and actions are determined by them.…”
Section: Centrality and Importance Of Some Attitudes And Beliefsmentioning
confidence: 99%